Sex discrepancies in pathophysiology, presentation, treatment, and outcomes of severe aortic stenosis - Stehli, Julia; Zaman, Sarah; Stähli, Barbara E. (Frontiers in Cardiovascular Medicine, 2023)
This review gives an overview of sex-based differences in aortic valve stenosis, spanning from pathophysiological mechanisms and disease progression, clinical presentation, presence of comorbidities, and diagnostic assessment, to treatment and outcomes. In particular, sex-related differences in the degree of aortic valve calcification, the response of the left ventricle to pressure overload, as well as in the referral to procedures, with women being less frequently referred for surgical aortic valve replacement and experiencing longer waiting times for transcatheter procedures, will be discussed. Sex-related differences are also particularly evident in outcomes of patients with severe aortic stenosis undergoing surgical or transcatheter procedures. The apparent sex paradox seen in women undergoing transcatheter aortic valve implantation refers to the phenomenon of women experiencing higher rates of short-term mortality and bleeding events, but demonstrating improved longterm survival as compared to men. Women who undergo surgical aortic valve replacement have generally worse outcomes as compared to men, which is reflected by the inclusion of female sex in surgical risk calculation scores. Hence, a thorough understanding of sex-related differences in aortic valve stenosis is important to provide optimal and personalized patient care.